2012
DOI: 10.1038/modpathol.2011.209
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical testing of conventional adenomas for loss of expression of mismatch repair proteins in Lynch syndrome mutation carriers: a case series from the Australasian site of the colon cancer family registry

Abstract: Debate continues as to the usefulness of assessing adenomas for loss of mismatch repair protein expression to identify individuals with suspected Lynch syndrome. We tested 109 polyps from 69 proven mutation carriers (35 females and 34 males) belonging to 49 Lynch syndrome families. All polyps were tested by immunohistochemistry for four mismatch repair proteins MLH1, MSH2, MSH6 and PMS2. Detailed pathology review was performed by specialist gastrointestinal pathologists. The majority of polyps (86%) were conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 28 publications
8
58
0
Order By: Relevance
“…Several prior studies have evaluated the diagnostic utility of IHC in adenomas from patients with known LS and found loss of staining by IHC in 60–80 % of adenomas [31, 33, 34]. Moreover, the presence of MMR deficiency is more prevalent in large adenomas (>8 mm) or those with advanced histologic features (high-grade dysplasia, villous histology); and over 90 % of polyps evaluated in our study met these criteria.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several prior studies have evaluated the diagnostic utility of IHC in adenomas from patients with known LS and found loss of staining by IHC in 60–80 % of adenomas [31, 33, 34]. Moreover, the presence of MMR deficiency is more prevalent in large adenomas (>8 mm) or those with advanced histologic features (high-grade dysplasia, villous histology); and over 90 % of polyps evaluated in our study met these criteria.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the presence of MMR deficiency is more prevalent in large adenomas (>8 mm) or those with advanced histologic features (high-grade dysplasia, villous histology); and over 90 % of polyps evaluated in our study met these criteria. In those settings, loss of MMR IHC expression exhibits a sensitivity of >90 % in identifying MMR deficiency [25, 31, 33, 34]. That said, the current findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 80%
“…18 Another study found that 80% of Lynch-associated adenomas were mismatch repair deficient by IHC. 19 This study identified a relationship between mismatch repair deficiency and a villous component or high-grade dysplasia, but not with size. At this point the available evidence suggests that mismatch repair deficiency in an adenoma is useful in identifying potential Lynch syndrome mutation carriers, but that the lack of mismatch repair deficiency in an adenoma is not as strong a criterion to exclude Lynch syndrome as the lack of mismatch repair deficiency in a cancer.…”
Section: Which Tumors Should Be Tested?mentioning
confidence: 81%
“…The ACCFR has been previously described, comprising a richly annotated cohort which includes MMR IHC information correlated with molecular data such as MSI status, MMR gene mutation status, MLH1 and CpG island methylator phenotype (CIMP) methylation analysis and BRAFV600E status determined by allele-specific PCR (AS-PCR). [36-38]. For this arm of the study CRC samples demonstrating loss of expression for MSH2 and/or MSH6 or solitary loss of PMS2 protein expression by IHC were excluded because of their very strong association with LS.…”
Section: Methodsmentioning
confidence: 99%